TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PELAKU PENGANIAYAAN YANG MENGAKIBATKAN LUKA BERAT DIBAGIAN KEPALA (PUTUSAN NOMOR : 317/PID.B/2018/PN.MDN) - Sialagan, David Seh Tumonggi; Simangunsong, Toni Wijaya; Sitepu, Yogie Ronaldo (jurnal.unprimdn.ac.id, 2019)
Criminal acts of torture are acts carried out in the form of attacks on the body or parts of the body that cause pain or injury, and even cause death. On this occasion, this paper aims to find out the application of criminal law to criminal acts of abuse that result in severe headaches. And to find out the legal considerations for judges in the imposition of criminal acts against perpetrators of criminal acts of abuse which resulted in serious injuries in the head in the case decision number 317 / PID.B / 2018 / PN MEDAN. To achieve these objectives the author uses data collection techniques with a literature study and the type of research carried out is normative juridical. The results of this study indicate the application of the law decided by the judge to the crime of abuse which resulted in severe head injuries. And the legal considerations of judges in imposing criminal sanctions must first be fulfilled elements of the article in the indictment and actions of judges to consider matters that alleviate and burden the defendants (perpetrators of the persecution).